Psychosocial mediators of perceived stigma and suicidal ideation among transgender women - Krishna Kiran Kota; Laura F. Salazar; Rachel E. Culbreth; Richard A. Crosby; Jamal Jones (BMC Public Health, 2020)
Abstract Background Transgender women (TGW) in the U.S. experience high rates of stigma, depression, and elevated rates of suicide. This study examined correlates of suicidal ideation and estimated the conditional indirect effects of perceived stigma and psychosocial mediators on suicidal ideation. Methods Using a cross-sectional study design, TGW (N = 92) were recruited through snowball sampling in Atlanta, Georgia. Structured interviews were conducted. Suicidal ideation was assessed by combining two variables that measured suicidal thoughts. Logistic regression models were performed to identify the potential risk and protective factors for suicidal ideation. We examined hypothesized psychosocial factors, including anxiety, depression, psychosocial impact of gender minority status, and substance use behaviors as potential mediators for the relationship between perceived stigma and suicidal ideation. All models were controlled for age, race, education, and homelessness. Results Suicidal ideation was reported by 33% (N = 30) of the study participants. In multivariable analysis, suicidal ideation was associated with sexual abuse (AOR = 3.17, 95% CI = 1.10–9.30), anxiety (AOR = 1.74, 95% CI = 1.10–2.73), family verbal abuse (AOR = 2.99, 95% CI = 1.10–8.40), stranger verbal abuse (AOR = 3.21, 95% CI = 1.02–10.08), and psychosocial impact of gender minority status (AOR = 3.42, 95% CI = 1.81–6.46). Partner support was found to be the protective factor for suicidal ideation (AOR = 0.34, 95% CI = 0.13–0.90). In the mediation analysis, the psychosocial impact of gender minority status mediated the relationship between perceived stigma and suicidal ideation. The estimated conditional indirect effect was 0.46, (95% CI = 0.12–1.11). Conclusion Interventions that aim to reduce suicidal behaviors among TGW should address stigma, psychosocial impact of gender minority status, and different forms of violence and abuse.